Continuous full-liquid-phase sulfide-based solid-state battery electrode slurry coating method
By mixing sulfide-based electrolyte precursors and active materials in a solvent using an all-liquid phase method, a sulfide-based electrode coating can be directly formed on the current collector. This solves the problems of time-consuming and labor-intensive ball milling and sintering, improves production efficiency and conductivity, and realizes the preparation of sulfide-based solid-state battery electrodes at high efficiency and low cost.
Patent Information
- Application Number
- CN202410976852.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2026-01-20
AI Technical Summary
In the preparation of sulfide-based solid-state battery electrodes, the ball milling and sintering processes in the existing technology are time-consuming and labor-intensive, resulting in low productivity and high cost, and the conductivity decreases after the solvent is mixed.
A fully liquid-phase method is used to directly form a sulfide-based electrode coating on the current collector by mixing sulfide-based electrolyte precursors, binders and active materials in a solvent, omitting the ball milling and sintering steps, and using the solvent to trigger the precursor chemical reaction to form the target electrolyte.
This improved preparation efficiency, reduced energy consumption and cost, while maintaining or improving electrode conductivity, thus enabling the production of high-performance sulfide-based solid-state battery electrodes.
Smart Images

Figure CN121366853A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a method of making a sulfide solid-state battery, and more particularly, to a full-liquid phase sulfide-based solid-state battery electrode slurry coating method. BACKGROUND
[0002] Compared to older types of rechargeable batteries, such as nickel-metal hydride batteries, nickel-cadmium batteries, or lead-acid batteries, rechargeable lithium-ion batteries have the ability to retain a relatively high energy density, a relatively low internal resistance, and a low self-discharge rate when not in use. Electric vehicles and hybrid vehicles primarily use rechargeable lithium-ion batteries as a reliable power source because lithium-ion batteries are capable of repeated power cycling over their useful life.
[0003] Solid-state batteries are a type of battery that uses a solid-state electrolyte (SSE) for ion conduction between electrodes and potentially offer higher energy density than typical lithium-ion batteries with liquid or gel polymer electrolytes. An all-solid-state battery (ASSB) is a battery that has no gas and liquid inside. All the components that make up the battery, including the electrodes and electrolyte, exist in a solid state. Sulfide-based ASSBs are promising as the next generation of batteries for electric vehicles due to their enhanced safety, potential for high energy density, and power capacity.
[0004] The fabrication of high-performance sulfide-based ASSBs faces challenges in terms of time, materials, and cost. In one particular embodiment, the sulfide-based SSE is synthesized prior to slurry mixing. The synthesis of the sulfide-based SSE includes the step of converting and mixing sulfide-based electrolyte precursors to achieve a relatively high target ionic conductivity using a ball-milling process followed by a sintering process. The dry synthesized sulfide-based SSE is then mixed with solvents, binders, active materials, and other ingredients to form an electrode slurry to coat electrode sheets. The milling of sulfide-based SSE precursors, sintering, and mixing into a slurry are both laborious and time-consuming, with the time potentially exceeding 24 hours, thus resulting in low productivity. The long milling process also consumes a large amount of energy, which leads to higher processing costs.
[0005] Therefore, while the conventional method of making sulfide-based ASSBs achieves its intended purpose, there is a need for a more efficient and more cost-effective process to make sulfide-based SSE electrodes for ASSBs. SUMMARY
[0006] According to several aspects, a method of making a solid-state electrode is disclosed. The method includes selecting precursors capable of undergoing a chemical reaction to form a target solid-state electrolyte (SSE), mixing the selected precursors into a solvent to form a coating slurry, applying the coating slurry onto a current collector, and evaporating the solvent in the coating slurry on the current collector, leaving a target SSE coating on the current collector. The precursors react in the solvent to form the target SSE in the coating slurry, thus eliminating the need for a prior ball-milling process to produce the SSE.
[0007] In another aspect of the disclosure, the coating slurry includes 30 weight percent (wt%) to 50 wt% of a solid, the solid including the selected precursors and one or more of a binder, an electrode active material, and a conductive carbon.
[0008] In another aspect of the disclosure, the solid includes 8.0 wt% to 38 wt% of the selected precursors, 2.0 wt% to 10 wt% of the binder, 60 wt% to 90 wt% of the electrode active material, and 1 wt% to 8 wt% of the conductive carbon.
[0009] In another aspect of the disclosure, the selected precursors are lithium sulfide (Li2S) and phosphorus pentasulfide (P2S5), and the target SSE is Li3PS4. The molar ratio of Li2S to P2S5 is 7:3 to 3:1.
[0010] In another aspect of the disclosure, the method further includes mixing Li2S and LiX into the solvent, where X is one of Cl, Br, and I. Li2S and LiX react in the solvent to form an argyrodite-type electrolyte. The molar ratio of Li2S to LiX is 1:1.
[0011] In another aspect of the disclosure, the method further includes mixing LiX, Li2S, and MS2 into the solvent, where M is selected from the group consisting of Si, Sn, and Ge. LiX, Li2S, and MS2 react in the solvent to form a lithium Si / Ge / Sn-phosphor sulfo-Halogen (LiMPSX).
[0012] According to several aspects, a method of making a sulfide-based solid-state electrode is provided. The method includes dissolving a binder in a first solvent to produce a binder solution, mixing a sulfur-electrolyte precursor in a second solvent for a mixing time greater than 2 hours, wherein the sulfur-electrolyte precursor reacts in the second solvent to produce a sulfur-electrolyte suspension, mixing the binder solution with the sulfur-electrolyte suspension to form a binder-sulfur-electrolyte suspension, mixing silicon powder and a third solvent into the binder-sulfur-electrolyte suspension to form an electrode coating slurry, applying the coating slurry onto a current collector, and drying the coating slurry on the current collector at a temperature of 60 °C to 160 °C, leaving a sulfur-electrolyte coated current collector. The sulfur-electrolyte precursor includes Li2S and P2S5. The first solvent, the second solvent, and the third solvent include tetrahydrofuran (THF).
[0013] In another aspect of the disclosure, the method further includes mixing conductive carbon into the electrode slurry.
[0014] In another aspect of the disclosure, a molar ratio of Li2S:P2S5 is 7:3 to 3:1.
[0015] In another aspect of the disclosure, the coating slurry includes between 30 wt% and 50 wt% total solids. The solids include Li2S and P2S5, binder, Si powder, and conductive carbon. The total solids include 15 wt% to 30 wt% Li2S and P2S5; 65 wt% to 80 wt% Si powder; 3.0 wt% to 7 wt% binder; and 2 wt% to 5 wt% conductive carbon.
[0016] According to several aspects, a method of making a sulfide-based solid-state negative electrode is provided. The method includes chemically reacting electrolyte precursors Li2S and P2S5 in a solvent to produce a sulfide-based electrolyte, wherein the solvent is styrene-ethylene-ethylene-propylene-styrene (SEEPS); mixing Si powder into the solvent; adding additional solvent to form an electrode coating; applying the electrode coating onto a copper foil; and drying the electrode-coated copper foil at a temperature of 80 °C to 160 °C, producing an electrode sheet having a sulfide-based solid-state electrolyte.
[0017] In another aspect of the disclosure, a weight ratio of Si, SEEPS, and Li2S and P2S5 is 70:5:25.
[0018] In another aspect of the disclosure, a molar ratio of Li2S to P2S5 is 3:1 and ball milling is not performed.
[0019] In another aspect of the disclosure, the electrode sheet having a sulfide-based solid-state electrolyte defines a negative electrode sheet.
[0020] Further areas of applicability will become apparent from the description provided herein. It should be understood that the description and specific examples are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. BRIEF DESCRIPTION OF DRAWINGS
[0021] The drawings described herein are for illustrative purposes only and are not intended to limit the scope of the present disclosure in any way.
[0022] Figure 1 is a graphical representation of a cross-section of a rechargeable sulfide-based solid-state battery according to an exemplary embodiment;
[0023] Figure 2 is a flow chart diagram of a first embodiment of a full-liquid phase sulfide-based solid-state battery electrode slurry coating method according to an exemplary embodiment;
[0024] Figure 3 is a flow chart diagram of a second embodiment of a full-liquid phase sulfide-based solid-state battery electrode slurry coating method according to an exemplary embodiment;
[0025] Figure 4 is a flow chart diagram of a third embodiment of a full-liquid phase sulfide-based solid-state battery electrode slurry coating method according to an exemplary embodiment;
[0026] Figure 5 is a flow chart diagram of a fourth embodiment of a full-liquid phase sulfide-based solid-state battery electrode slurry coating method according to an exemplary embodiment;
[0027] Figure 6A 、 Figure 6B and Figure 6C are performance plots of sulfide-based solid-state batteries having electrodes fabricated by the method of Figure 3 DETAILED DESCRIPTION
[0028] The following description is merely exemplary in nature and is not intended to limit the present disclosure, application, or uses. The illustrated embodiments are disclosed with reference to the drawings, wherein like reference numerals designate corresponding parts throughout the several views. The drawings are not necessarily to scale, and some features can be exaggerated in order to show details which could not be readily discernible in a smaller scale drawing. The disclosed specific structures and functions described herein are not meant to be limiting but are exemplary embodiments to teach one skilled in the art how to practice the disclosed concepts.
[0029] When an element or layer is referred to as being “on,” “engaged to,” “connected to,” “attached to,” or “coupled to” another element or layer, it can be directly on, engaged, connected, attached, or coupled to the other element or layer, or one or more intervening elements or layers can be present. In contrast, when an element is referred to as being “directly on,” “directly engaged to,” “directly connected to,” “directly attached to,” or “directly coupled to” another element or layer, then there are no intervening elements or layers present. Other words used to describe the relationship between elements should be interpreted in a like fashion (e.g., “between” versus “directly between,” “adjacent” versus “directly adjacent,” etc.). As used herein, the term “and / or” includes any and all combinations of one or more of the associated listed items.
[0030] The terms “first,” “second,” “third,” etc. can be used herein to describe various elements, components, regions, layers and / or sections. Such elements, components, regions, layers and / or sections should not be limited by such terms. Such terms can be used merely to distinguish one element, component, region, layer or section from another region, layer or section. Terms such as “first,” “second,” and other numerical terminology do not imply a sequence or order unless specifically recited in the context to do so. Thus, a first element, component, region, layer or section discussed below could be termed a second element, component, region, layer or section without departing from the teachings of the example configurations.
[0031] Figure 1 is an illustration of a rechargeable solid-state battery, generally designated by reference numeral 100. In non-limiting embodiments, the SSB 100 can be an all-solid-state battery (ASSB). The SSB 100 includes a negative electrode 102, a positive electrode 104, and a separator layer 108 disposed between the negative electrode 102 and the positive electrode 104. The separator layer 108 includes a solid-state electrolyte material suitable for conducting lithium ions between the negative electrode 102 and the positive electrode 104.
[0032] The negative electrode 102 includes a lithium-accepting host material 103, and the positive electrode 104 includes a lithium-based active material 105 that can store lithium ions at a higher potential than the lithium-accepting host material 103 of the negative electrode 102. One or both of the negative electrode 102 and the positive electrode 104 can also include sulfur compounds, such as metal sulfides, sulfide-based electrolytes, and other lithium-conducting sulfur compounds.
[0033] The positive electrode 104 is also referred to as the cathode 104 due to its higher electrochemical potential, while the negative electrode 102 is also referred to as the anode 102 due to its relatively lower electrochemical potential. Each of the negative electrode 102 and the positive electrode 104 is housed by a respective current collector 112, 114. The current collectors 112, 114 can be connected by an interruptible circuit 120 that allows current to pass between the negative electrode 102 and the positive electrode 104 to electrically balance the associated migration of lithium ions between the negative electrode 102 and the positive electrode 104 through the separator layer 108. The current collectors 112, 114 can be formed of a metal foil. The metal foil can be formed of an electrically conductive metal, such as copper for the negative electrode and aluminum for the positive electrode.
[0034] A conventional method of preparing a coating slurry for coating a current collector to form an electrode requires pre-preparation of a solid state electrolyte (SSE), which is then mixed with a solvent to form the coating slurry. The pre-preparation of the SSE typically includes ball milling of precursors to form an electrolyte and sintering of the electrolyte to produce SSE particles having a desired ionic conductivity. The SSE particles are then mixed with a solvent to form the coating slurry. The coating slurry is applied to the current collector, and then the solvent is evaporated to produce an electrode sheet having the SSE.
[0035] Ball milling is a mechanical process that involves high-speed rotation of a drum containing milling media, typically ceramic balls. Sulfide-based electrolyte precursors, such as lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), lithium chloride (LiCl), and a solvent are loaded into the drum. As the drum rotates, the milling media collide with the sulfide-based electrolyte precursors, causing them to break down and reduce in size. The sulfide-based electrolyte precursors chemically react with each other under the heat generated by the ball milling process to form a sulfide-based electrolyte mixture. The milling time required is typically more than 24 hours.
[0036] After ball milling, the sulfide-based electrolyte mixture is sintered at about 550°C to obtain a sulfide-based solid state electrolyte (SSE) having an ionic conductivity greater than E-3 mS / cm. The sulfide-based SSE is then mixed with a solvent, a binder material, and an active material to form an electrode coating slurry, also referred to as an electrode slurry or a coating slurry. The electrode slurry is coated onto a current collector. The solvent in the electrode slurry is evaporated, leaving behind a sulfide-based SSE having an ionic conductivity of E-4 mS / cm. A disadvantage of this conventional method is the time and energy required for the ball milling process and sintering of the milling material. Another disadvantage is the addition of a solvent in the milling material to form the electrode slurry, which reduces the ionic conductivity of the sintered solid state electrolyte, for example, from E-3 mS / cm to E-4 mS / cm.
[0037] During ball milling, the heat generated during ball milling causes the electrolyte precursor to undergo a solid-solid reaction. The solid-solid reaction is an endothermic reaction that requires significant bond breaking and reorganization of the precursors to form the electrolyte particles. The present disclosure provides a simple and cost-effective continuous all-liquid phase sulfide solid-state battery electrode slurry coating method. The method of the present disclosure eliminates the ball milling and sintering steps in the electrode slurry coating fabrication, which has similar, if not better, electrical conductivity than the electrode coating fabricated with the traditional ball milling method.
[0038] The overview of the continuous all-liquid phase sulfide solid-state battery electrode slurry coating method (method 200) includes: fabricating an electrode coating slurry, coating a current collector with the electrode coating slurry, and evaporating the solvent in the coated current collector, leaving a solid-state electrolyte (SSE) coated current collector, also referred to as an electrode sheet. Fabricating the electrode coating slurry or coating slurry includes: mixing solids including precursors for forming a target electrolyte and at least one of a binder, an active material, and a conductive carbon in a solvent, and adjusting the solids to form an electrode slurry. Sufficient solvent is added to the mixture to form the electrode slurry with an effective consistency for coating the current collector. The solvent triggers a chemical reaction of the precursors to produce the target electrolyte in the solvent. In a non-limiting embodiment, the target electrolyte is a sulfide-based electrolyte Li6PS5Cl produced by the chemical reaction of the precursors Li2S, P2S5, and LiCl in the solvent. The solvent is evaporated from the coating slurry, leaving the sulfide-based SSE.
[0039] Figure 2 A block diagram showing a first embodiment of the method 200 is shown. The first embodiment of the method 200 is referred to as method 200A. In block 202A, a sufficient amount of a binder is dissolved in a solvent to form a binder solution. Moving to block 204A, selected precursors of a target SSE are added to the binder solution and mixed for more than 2 hours to form a binder-sulfur-electrolyte suspension. Moving to block 206A, an electrode active material, such as silicon (Si), and a sufficient amount of additional solvent are added to the binder-sulfur-electrolyte suspension to form a coating slurry having 30 to 50 weight percent (wt%) of total solids and the remaining 70 to 50 wt% of solvent. Moving to block 208A, a planar metal foil, i.e., a current collector, is coated with the coating slurry. The coating slurry on the metal foil is dried at a temperature of about 60 to 200 °C, preferably about 80 to 160 °C, resulting in an electrode sheet having the SSE.
[0040] Figure 3A block diagram showing a second embodiment of the method 200. The second embodiment of the method 200 is referred to as method 200B. In block 202B, a sufficient amount of binder is dissolved in a first solvent to form a binder solution. Meanwhile, in block 204B, a sufficient amount of a second solvent is added to a predetermined amount of a sulfur-electrolyte precursor and mixed for more than 2 hours during which the precursor reacts to produce a sulfur-electrolyte to form a sulfur-electrolyte suspension. Move to block 206B, the binder solution is mixed with the sulfur-electrolyte suspension to form a binder sulfur-electrolyte suspension. Move to block 208B, a predetermined amount of an electrode active material and a solvent are added to the binder sulfur-electrolyte suspension. Move to block 210B, the binder sulfur-electrolyte suspension, Si, and the solvent are thoroughly mixed with a third solvent to form a coating slurry. The first, second, and third solvents can be the same type of solvent. Move to block 212B, a planar metal foil, i.e., a current collector, is coated with the coating slurry. The coating slurry on the metal foil is dried at a temperature of about 60°C to 200°C, preferably about 80°C to 160°C, thereby producing an electrode sheet having SSEs.
[0041] Figure 4 A block diagram showing a third embodiment of the method 200. The third embodiment of the method 200 is referred to as method 200C. In block 202C, a sufficient amount of a solvent is added to dissolve a predetermined amount of a binder to form a binder solution. In block 204C, a sufficient amount of an electrode active material, such as Si powder, and a solvent are added to form a binder / Si suspension. Move to block 206C, a precursor Li2S, P2S5, etc., and additional solvent are added to the binder / Si suspension. Move to block 208C, the binder / Si suspension, the precursor, and the solvent are thoroughly mixed to form a coating slurry. Move to block 210C, a planar metal foil, i.e., a current collector, is coated with the coating slurry. The coating slurry on the metal foil is dried at a temperature of about 60°C to 200°C, preferably about 80°C to 160°C, thereby producing an electrode sheet having SSEs.
[0042] Figure 5 A block diagram showing a fourth embodiment of the method 200. The fourth embodiment of the method 200 is referred to as method 200D. In block 202D, a binder, Si, and a precursor (Li2S, P2S5, etc.) are introduced into a solvent and then mixed for more than 2 hours to form a coating slurry. The coating slurry on the metal foil is dried at a temperature of about 60°C to 200°C, preferably 80°C to 160°C. Move to block 206D, a planar metal foil, i.e., a current collector, is coated with the coating slurry. The coating slurry on the metal foil is dried at a temperature of about 60°C to 200°C, preferably about 80°C to 160°C, thereby producing an electrode sheet having SSEs.
[0043] For each embodiment of the method 200 (200A, 200B, 200C, 200D), the precursors of the target electrolyte are mixed in a solvent in a predetermined molar ratio to react, thereby producing the target electrolyte in the solvent. The solvent triggers and mediates the chemical reaction of the precursors to form the target electrolyte. In one non-limiting example, the selected precursors Li2S and P2S5 are mixed in a THF solvent in a ratio of 3 moles of Li2S to 1 mole of P2S5 (molar ratio of 3:1). During the mixing process, the selected precursors Li2S and P2S5 chemically react in the solvent to form the target Li3PS4. In another example, the selected precursors Li2S, P2S5, and LiCl are mixed in a p-xylene solvent and chemically react in the solvent to form the target Li6PS5Cl.
[0044] Examples of solvents that can be used to implement the reaction of the sulfide-based SSE precursors to produce the sulfide-based electrolyte include, but are not limited to, tetrahydrofuran (THF), 2-methyltetrahydrofuran (MeTHF), dimethoxyethane (DME), p-xylene, anisole, acetonitrile (ACN), toluene, heptane, ethyl acetate (EA), and the like.
[0045] Binders that can be used for each embodiment of the method 200 (200A, 200B, 200C, 200D) include, but are not limited to, nitrile butyl rubber (NBR), hydrogenated nitrile butyl rubber (HNBR), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene-butadiene rubber (SBR), polyvinylidene fluoride-trifluoropropylene copolymer (PVDF-TFP), SEPTON plastics (e.g., styrene-ethylene-ethylene-propylene-styrene (SEEPS), styrene-butadiene-styrene (SBS), styrene-ethylene-butylene-styrene (SEBS), and the like).
[0046] In a non-limiting example of the coated slurry made by the above-described methods, the coated slurry includes 30 wt% to 50 wt% total solids and 50% to 70% solvent. The total solids include the precursors as well as one or more of a binder, an electrode active material, and conductive carbon. The precursors, such as Li2S and P2S5, are present in a proportion of 8.0 wt% to 38 wt%, preferably 15 wt% to 30 wt%, of the total solids. The molar ratio of Li2S to P2S5 is 7 / 3 to 3 / 1. The binder is present in a proportion of 2.0 wt% to 10 wt%, preferably 3.0 wt% to 7 wt%, of the total solids. The electrode active material, such as Si powder, is present in a proportion of 60 wt% to 90 wt%, preferably 65 wt% to 80 wt%, of the total solids. The slurry can also include conductive carbon in a proportion of 1 wt% to 8 wt%, preferably 2 wt% to 5 wt%, of the total solids.
[0047] The electrode active material for the negative composition can include Si:SEEPS:(Li2S+P2S5) in a weight ratio of 70:5:25. Wherein the molar ratio of Li2S / P2S5 is 3 / 1. The electrode active material for the positive composition includes LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523):LPSCl:SP.
[0048] In another non-limiting embodiment, LiX (X = Cl, Br, I) and Li2S can be added to a solvent to form a argyrodite-type electrolyte (e.g., a molar ratio of LiCl / Li2S is 1 / 1). In another non-limiting embodiment, LiX, Li2S, and MS2 (M = Si, Sn, Ge) can be added to a solvent to form a lithium Si / Ge / Sn-phosphosulfo-halide (LiMPSX).
[0049] Figure 6A 、 Figure 6B and Figure 6C is a performance plot of a solid-state battery with a sulfide-based SSE negative electrode made by method 200 compared to a solid-state battery with a negative electrode made by a traditional method. The traditional method includes ball milling followed by addition of solvent to make a coating slurry. Figure 6A is an initial charge-discharge curve of a solid-state battery at 0.05C rate. This shows that the electrode employing method 200 can have a slightly higher initial discharge capacity. Figure 6B is a discharge test of a battery at different discharge rates. This shows that method 200 can enable a negative electrode with better discharge power capacity, which stems from the improvement of electrical conductivity within the electrode. Figure 6C The room temperature cycling performance of the battery at 0.5C is compared. Method 200 has good cycling stability.
[0050] Numerical data presented in the description is presented in range format. The term “about” is used herein to indicate that a value includes the standard deviation of the mean. Alternatively, the term “about” encompasses a range of values falling within 0.5% of the specified value. It is to be understood that the range format is used only for convenience and brevity and should be interpreted in a flexible manner to include not only the numerical values explicitly recited as the limits of a range, but also to include all the individual numerical values or sub-ranges within that range as if each numerical value and sub-range is explicitly recited. While embodiments have been described in detail, those familiar with the art will recognize that various substitutions and alterations are
[0051] The description of the present disclosure is merely exemplary in nature and variations that do not depart from the spirit and scope of the present disclosure are intended to be within the scope of the present disclosure. Such variations are not to be regarded as a departure from the spirit and scope of the present disclosure.
Claims
1. A method for fabricating a solid electrode, comprising: Select precursors that can undergo chemical reactions to form the target solid electrolyte (SSE); The selected precursor is mixed into a solvent to form a coating slurry, wherein the precursor reacts in the solvent to form the target SSE in the coating slurry; The coating slurry is applied to the current collector; as well as The solvent in the coating slurry on the current collector is evaporated, thereby leaving a target SSE coating on the current collector.
2. The method according to claim 1, wherein, The selected precursor is not subjected to a ball milling process.
3. The method of claim 1, further comprising mixing at least one of an adhesive, an electrode active material, and conductive carbon into the solvent to form the coating slurry.
4. The method according to claim 3, wherein, The coating slurry comprises 30 to 50 wt% solids, wherein the solids include the selected precursor and at least one of the binder, the electrode active material, and the conductive carbon.
5. The method according to claim 4, wherein, The solid material includes: 8.0 wt% to 38 wt% of selected precursors; 2.0 wt% to 10 wt% of the adhesive; The electrode active material comprises 60 wt% to 90 wt%; and The conductive carbon is 1 wt% to 8 wt%.
6. The method according to claim 1, wherein, The selected precursors are lithium sulfide (Li2S) and phosphorus pentasulfide (P2S5), and the target SSE is Li3PS4.
7. The method according to claim 6 further comprises a molar ratio of Li2S to P2S5 of 7:3 to 3:
1.
8. The method of claim 6, further comprising mixing Li₂S and Liₓ into the solvent, wherein, X is one of Cl, Br, and I; and Li2S and LiX react in the solvent to form a sulfogermanium ore-type electrolyte.
9. The method according to claim 8 further comprises a molar ratio of Li2S to LiX of 1:
1.
10. The method of claim 6, further comprising mixing LiX, Li2S, and MS2 into the solvent, wherein, M is selected from the group consisting of Si, Sn, and Ge; and LiX, Li2S, and MS2 react in the solvent to form lithium Si / Ge / Sn-phosphorus sulfonyl halogen (LiMPSX).